PENERAPAN PROJECT WORK PADA MATA KULIAH KAIWA MAHASISWA BAHASA JEPANG FKIP UNRI - Dini Budiani; Merri Silvia Basri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
This study aims to improve communication skills, in learning conversation(kaiwa) in Japanese language student of teacher training and education faculty Riau University.Many conversation exercises are only focused on practising sentence pattern and memorizing ofconversation examples contained in the textbook. Thus learning pattern causes learners not to beable to express what they want to convey in the real scope of communication in Japaneselanguage. This study tries to overcome the problem by implementing project work inconversation lectures. The purpose of this study is to see the involvement of learners in thelectures using project work and find out their opinions about the method. The data of this studywere 44 students of Japanese Language Education Study Program of Teacher Training andEducation Faculty Riau University. From the result of the study, it was seen that during theproject work implementation the learners were actively involved in learning even though theyexperience language barrier when communicating. From the result of the questionnaire thatasked about learners’ opinion, it was found that almost all learners had a positive impression ofthe project work on the Kaiwa 4 subject.